Advanced lightweight periclase-magnesium aluminate spinel refractories with high mechanical properties and high corrosion resistance. (12th July 2021) - Peng, Wangding; Chen, Zhe; Yan, Wen; Schafföner, Stefan; Li, Guangqiang; Li, Yawei; Jia, Cangjian
Highlights: The lightweight refractory using microporous magnesia aggregates was fabricated. A new strategy to improve mechanical properties of refractories for cement kiln. Cement clinker corrosion mechanisms of lightweight refractory were clarified. The advanced refractories had a high strength and a high cement clinker resistance. Abstract: A new strategy to improve the mechanical strength and the cement clinker corrosion resistance of refractories for cement kiln was proposed in this work. For this purpose, advanced lightweight periclase-magnesium aluminate spinel refractories (LPSR) with high mechanical properties and excellent cement clinker resistance were fabricated using microporous magnesia aggregates. Their microstructures and properties were then compared to conventional dense periclase-magnesium aluminate spinel refractories (DPSR) containing sintered magnesia aggregates. The apparent porosities of the microporous and dense magnesia aggregates were 43.1% and 5%, respectively. Scanning electron microscopy observation results showed that the interface between the microporous aggregates and the matrix was better, which significantly improved the strength and thermal shock resistance of the LPSR. Additionally, the microporous magnesia aggregates absorbed some of the penetrating slag from the matrix, which prevented further infiltration. Thus, after substituting the microporous magnesia aggregates for dense magnesia aggregates to fabricate LPSR, the practically same cement clinker resistance was obtained for the LPSR compared to DPSR. Meanwhile, the bulk density was decreased from 2.87 g/cm 3 to 2.61 g/cm 3, while the compressive strength and flexural strength increased from 48.7 MPa to 73.1 MPa and 6.0 MPa to 10.1 MPa, respectively. Meanwhile, practically the same cement clinker resistance was obtained for the LPSR compared to DPSR.